2007
DOI: 10.1111/j.1365-2141.2007.06618.x
|View full text |Cite
|
Sign up to set email alerts
|

A practical strategy for the routine use of BIOMED‐2 PCR assays for detection of B‐ and T‐cell clonality in diagnostic haematopathology

Abstract: SummaryBIOMED-2 polymerase chain reaction (PCR) assays for clonality analysis of immunoglobulin (IG) and T-cell receptor (TCR) gene rearrangements were evaluated in routine haematopathological practice where paraffin-embedded tissues constitute the majority of specimens. One hundred and twenty-five fresh/frozen and 316 paraffin specimens were analysed for DNA quality and clonality. Seventy-nine per cent of paraffin specimens yielded PCR products of over 300 bp. These specimens and all fresh/frozen specimens we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 35 publications
6
106
3
Order By: Relevance
“…22 For FFPE samples, the sensitivity has been reported to range from 80 to 98% for TCR. [23][24][25][26] ENKTLs are frequently accompanied by necrosis and apoptosis of the tumor cells, leading to degradation of DNA, ineffective PCR reactions, and false-negative results. 27 In a study by Pongpruttipan et al, 8 clonal TCR gene rearrangements were documented in only three out of six TCR protein-positive cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 For FFPE samples, the sensitivity has been reported to range from 80 to 98% for TCR. [23][24][25][26] ENKTLs are frequently accompanied by necrosis and apoptosis of the tumor cells, leading to degradation of DNA, ineffective PCR reactions, and false-negative results. 27 In a study by Pongpruttipan et al, 8 clonal TCR gene rearrangements were documented in only three out of six TCR protein-positive cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cell types of extranodal NK/T-cell lymphoma M Hong et al 17,26 recent studies using immunohistochemistry showed variable degrees of TCR expression, ranging from 0 to 23% of these tumors. 7,8,10,20 Rodriguez-Pinilla et al 10 showed that ENKTLs primarily affecting the skin or subcutaneous tissue (n = 11) were all negative for TCR-γ.…”
Section: Modern Pathology (2016) 29 430-443mentioning
confidence: 99%
“…This was performed by PCR of variably sized genomic fragments (Table 1), 14 using a 2-ng template DNA in a 10-mL reaction mixture. PCR conditions were 95 C for 10 minutes, 40 cycles of 95 C for 20 seconds, 60 C for 20 seconds, 72 C for 1 minute, and a final extension at 72 C for 5 minutes.…”
Section: Assessment Of Dna Quality By Conventional Pcrmentioning
confidence: 99%
“…DNA was extracted by using standard proteinase K digestion, followed by phenol/chloroform/ isoamyl-alcohol extraction or by using the QIAamp DNA Micro Kit (QIAGEN). The quality of the DNA samples was assessed by the PCR amplification of variably sized gene fragments (33), and those with successful amplifications of genomic fragments in excess of 300 bp, in addition to the DNA samples from the frozen tissues, were used for mutational screening.…”
Section: Microdissection and Dna Preparationmentioning
confidence: 99%